A new genus and four new species of millipedes from Tasmania, Australia (Diplopoda: Polydesmida: Dalodesmidae), with notes on male leg setae in some Tasmanian dalodesmids - Mesibov, Robert (Zootaxa, 2004)
Bromodesmus catrionae n. gen., n. sp. (type species), B. militaris n. sp., B. riparius n. sp. and B. rufus n. sp. are described. The new genus is characterized by greatly reduced paranota and a gonopod telopodite expanded at the distal end into a posteriorly concave hood fringed with teeth; the hood partly protects a long, curved, acutely pointed solenomerite. Male leg setation in the type species of six Tasmanian dalodesmid genera is briefly discussed and illustrated with scanning electron micrographs. The sphaerotrichome shaft is sharply pointed in Atrophotergum; gently tapered in Dasystigma, Lissodesmus and Tasmanodesmus; expanded at the tip in Bromodesmus; and entirely absent in Gasterogramma. Tips of the setae forming the dense ventral brush on male podomeres are gently tapered in Dasystigma and Lissodesmus, truncated in Gasterogramma, expanded in Bromodesmus and forked in Tasmanodesmus.